Reduction of the effect of internal activity in LaCl3:Ce scintillator. (21st June 2021) - Chattopadhyay, D.; Sharma, S.; Saha Sarkar, M.
Abstract: Despite having excellent energy and time resolutions, the intrinsic α and β contaminations in the lanthanum halide scintillators pose severe limitations in their usage in rare-event detections, especially. In the present work, pulse shape discrimination (PSD) with a pre-defined algorithm of a commercially available fast digitizer has been utilized to separate the effect of α contamination from the spectrum. The efficacy of the method has been measured experimentally and compared with simulation. The contribution of the β activity has been eliminated by generating its shape with the help of a Monte-Carlo based simulation code. Thus the background events generated by intrinsic β and α activities have been reduced appreciably. The present study will encourage the application of these detectors in low cross-section measurement experiments.